Linker phosphoramidite reagents for the attachment of the first nucleoside to underivatized solid-phase supports - Pon, Richard T. (Oxford University Press, 2004)
New linker phosphoramidite reagents containing a cleavable 3′-ester linkage are used for attaching the first nucleoside to the surface of a solid- phase support. Inexpensive, underivatized amino supports, such as long chain alkylamine controlled-pore glass, can serve as universal supports. No modifications to phosphoramidite coupling conditions are required and, after synthesis, treatment with NH(4)OH releases the products with 3′-OH ends. No 3′-dephosphorylation is required. Phosphoramidite reagents containing a succinate and sulfonyl diethanol linkage between the nucleoside and phosphoramidite group are particularly advantageous and can be used to create both 3′-OH and 5′-phosphate ends on oligonucleotides. Reproducibility and quality of oligonucleotide synthesis is demonstrated for either column and 96-well plate formats on low-, medium- or high-loading CPG supports.